Using Multimedia In Interactive Learning: A Comparative Study On Its Impact On Student Learning In The CD-Based And Web-Based Domains - Teoh, Belinda Soo Phing (2006)
In this research project, the focus will be on a comparative study on the impact on student learning when interactive multimedia educational content is delivered to the student via the CD and the Web. A set of multimedia tools will be employed to create the student learning environments. The essential features of these learning strategies will be documented, examined and its impact on the student learning process assessed.